Survey of the Early (pre-1000 AD) Use of Christian Saints’ Names and Images on European Coins - Spenciner, David B.; Dziemianowicz, Theodore (KOINON: The International Journal of Classical Numismatic Studies, 2023)
While the very earliest appearance of a Christian Saint has been well described as Saint Michael replacing winged Liberty on gold Tremisses of Lombardy in the late 7th and early 8th Century, other saints also appeared in multiple places across Europe very soon thereafter. The study goal was to identify and categorize this very early use of Christian saint’s names and images on European coins. In total, 19 numismatic books representing ten geographic regions were analyzed and the appearance of saints, either in the inscription or as a portrait, was noted. A total of 157 coin types mentioning 19 different saints were identified as dating to before the year 1000 AD. Mints in several regions were represented, including parts of Italy, France, England, the Low Countries, and Germany/Austria, with the very first coins minted starting in Pavia and featuring both an image and the name of Saint Michael.